A Interaksi Psikoneuroimunologi: Dampak Stres Psikologis terhadap Fungsi Imunologis - Pauzan; Muhammad Khalid Iswadi; Idham Halid (Postgraduate, University of Mataram, 2025)
Psychological stress plays a crucial role in modulating the immune system through complex mechanisms involving interactions between the nervous, endocrine, and immune systems. This review evaluates the impact of acute and chronic stress on immune function and the molecular pathways involved. This study employed a narrative literature review approach to explore the relationship between psychological stress and the immune system from a psychoneuroimmunological perspective. The literature review found that chronic stress has been shown to induce immune system dysregulation through activation of the hypothalamic-pituitary-adrenal (HPA) axis and the sympathetic nervous system, leading to increased levels of glucocorticoid and catecholamine hormones. These hormones influence immune cells, inhibiting the proinflammatory Th1 pathway, enhancing the Th2 response, and causing increased levels of inflammatory cytokines such as IL-6 and TNF-α. Consequently, stress contributes to an increased risk of chronic diseases such as cardiovascular disease, cancer, depression, and diabetes. Meanwhile, short-term acute stress can have adaptive immunostimulatory effects, especially in healthy individuals. The stress response is highly individualized and influenced by a person's biological vulnerability and coping capacity. By understanding the relationship between stress and the immune system in the context of psychoneuroimmunology, preventive approaches and clinical interventions can be developed to minimize the adverse effects of stress on physical and mental health.